2022
DOI: 10.1002/jdd.13018
|View full text |Cite
|
Sign up to set email alerts
|

Advancing women, parity, and gender equity

Abstract: For centuries, society has called out for transformations to lift all of its members. While it may seem ordinary in our time for women to be dentists or dental educators, the path was neither always easy, nor has true equity been achieved. The modern transformation of dental education and dentistry creates the need for leaders to propose and develop concrete initiatives to advance the profession and benefit society. Areas to address that could lead to increased equity for women include career advancement, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Various studies have explored gender disparities in academic dentistry and have identified that women faculty experience reduced academic productivity, delays in promotion, and poor retention-but, why? [4][5][6][7][8] This discussion will focus on elevating the perspectives and lived experiences shared by women dental faculty in this study to better understand the drivers of gender inequities in dental education. Further, recommendations from women dental academics will be shared to highlight actionable ways in which barriers to career advancement can be dismantled and the aspirations of women in academic dentistry can be better supported.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have explored gender disparities in academic dentistry and have identified that women faculty experience reduced academic productivity, delays in promotion, and poor retention-but, why? [4][5][6][7][8] This discussion will focus on elevating the perspectives and lived experiences shared by women dental faculty in this study to better understand the drivers of gender inequities in dental education. Further, recommendations from women dental academics will be shared to highlight actionable ways in which barriers to career advancement can be dismantled and the aspirations of women in academic dentistry can be better supported.…”
Section: Discussionmentioning
confidence: 99%
“…As has been widely reported, this might be due to a lack of women practicing dentistry, who can also serve as role models for the future generation. Indeed, it is reported that when a woman takes on a leadership position in dentistry, she has less probability of being married or with children [ 3 , 4 , 5 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. This scenario frightens new generations of young women who see themselves as forced to choose between a career or family, which is a scenario that young men do not perceive [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent data indicate that the percentage of women dental school graduates has slightly increased from 46% to 50.6% between 2009 and 2019 12 . Additionally, between 2010 and 2020, the percentage of women in the dental workforce increased from 24.1% to 34.5% 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent data indicate that the percentage of women dental school graduates has slightly increased from 46% to 50.6% between 2009 and 2019 12 . Additionally, between 2010 and 2020, the percentage of women in the dental workforce increased from 24.1% to 34.5% 12 . Correspondingly, 2019 saw a rise in woman representation in dental academia to 37% in dental school and 85% in allied‐dental‐program faculty 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation